ChemInform Abstract: Oxidative Cyclizations, the Synthesis of Aryl‐Substituted C‐Glycosides, and the Role of the Second Electron Transfer Step. Issue 17 (28th April 2014) - Smith, Jake A.; Moeller, Kevin D.
Abstract Anodic oxidation reactions are used to synthesize aryl‐substituted C‐glycosides.